Thematic Study of the Qur’an, an Analysis of the Works of the 21st Century in the Western Academia (Al Basirah, 2025)
Tafsīr is one of the earliest and most noble discipline among the traditional sciences. Within this genre, multiple methodologies, such as analytical, comparative and thematic, have been introduced to understand the word of Allah.  Although the roots of Thematic study trace back to the traditional era, it has flourished remarkably in the past two centuries. Recent Muslim scholars such as Abdullah Draz, Muhammad Baqir al Sadr, and Muhammad Al Sharawi produced significant works discussing the Qur’ān's themes in relation to contemporary issues, such as economics, human rights, and the environment. Hence, they managed to provide a holistic Qur’ānic approach towards the recent problems. The Western scholars, such as Jacques Jomier (d. 2008), Jane Demmen McAuliff, Andrew Rippin, Daniel A. Madigan, have shown a growing interest in thematic study of the Qur’ān leading to the production of numerous influential books and articles. Hence, A drastic shift from historical study of the Qur’ān to its textual and thematic study can be observed in the past and the present century. The present article aims to highlight this significant development in the study of the Qur’ān in the West. Moreover, a critical analysis of some renowned works is offered along with the brief introduction. The author has selected four major western academic works (by non-Muslim scholars) of the present century that has gained scholars' attention from all over the globe in the genre of the Qur'anic studies. This paper suggests that, although Western academia has made significant steps in refining its style and language, adopting a more respectful and academically nuanced tone, but due to various internal and external factors, this does not necessarily mean that the conclusions they present, align with those of the mainstream Muslim scholarship. The primary reasons, among many others, may be—though not in all cases—the influence of deeply rooted past ideas about the Qur'an and diversity of writers’ backgrounds. The paper concludes that adopting a more objective and academic approach towards the Qur'an and its themes may help bridge the intellectual gap between the two worlds
Keywords: Qur’ān; West; Thematic study; Encyclopedia; Comparative Study